Biosorption of nickel ions Ni2+ by natural and modified Pinus caribaea Morelet sawdust. Issue 2 (February 2022) - Sinyeue, Cynthia; Garioud, Théophile; Lemestre, Monika; Meyer, Michaël; Brégier, Frédérique; Chaleix, Vincent; Sol, Vincent; Lebouvier, Nicolas
Abstract: The potential of Pinus caribaea Morelet sawdust for the removal of nickel ions (Ni 2+ ) and other metallic trace ions (Co 2+, Cr 3+, Mn 2+ ) from aqueous solutions was investigated under batch conditions. Several parameters such as size of particles, contact time, pH, initial metal and biomass concentrations, desorption conditions and reusability were evaluated on natural biomass. Biosorption was fast, effective (73%) and biomaterial can be reused after five cycles. To enhance the removal capacity of nickel, pine sawdust was modified by acidic and oxidative treatments. Cellulosic residues from sawdust sequential extraction showed great biosorption capacity (96%). In the presence of a metal mixture, oxidized sawdust had better selectivity for Cr 3+ ions than for Ni 2+ . Pinus caribaea biomass could be an environmental, inexpensive and renewable material for the depollution of water laden with metallic trace elements. Graphical abstract: Image 1 Highlights: Pinus caribaea sawdust is an effective biosorbent of metallic trace elements. High Ni 2+ removal efficiency was observed at pH 8 with 5 g/L of biosorbent. Equilibrium adsorption was described by Freundlich and Langmuir isotherms. Pine sawdust is a reusable biosorbent with good desorption capacity. Efficiency of acidified and oxidized adsorbents. Abstract : Nickel, Pinus caribaea Morelet, Modified sawdust, Biomass recycle, Water treatment.